PENGARUH KOMUNIKASI PEMASARAN, KEBUTUHAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PRODUK UMKM DI KOTA BENGKULU - Arini, Eti; Andrayani, Yora (UM. Bengkulu, 2024)
The purpose of this study was to determine the effect of marketing communications, needs and location on purchasing decisions for MSME products in Bengkulu City (Case Study of Batik Al-Sufi UMKM). This research is a type of quantitative research. Data collection techniques are observation, documentation and questionnaires. Data analysis techniques using descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The results showed that marketing communications had a positive effect on purchasing decisions at the Al-Sufi Batik Shop in Bengkulu City, thus the higher the marketing communications, the higher the purchasing decision at the Al-Sufi Batik Shop in Bengkulu City. The need has a positive effect on the purchasing decision of the Al-Sufi Batik Shop, Bengkulu City, thus the higher the need, the higher the purchase decision at the Al-Sufi Batik Shop, Bengkulu City. Location has a positive effect on the purchasing decision of the Al-Sufi Batik Shop, Bengkulu City, thus the higher the location, the higher the purchasing decision at the Al-Sufi Batik Shop, Bengkulu City. Marketing communications, needs and location together show an influence on purchasing decisions at the Al-Sufi Batik Shop, Bengkulu City. Keywords: Marketing communication, needs, location, purchase decision